Carrier-wave population transfer in semiconductors. Issue 8 (January 2020) - Zuo, R; Song, X; Meier, T; Yang, W
Synopsis: We show that a novel carrier-wave population transfer, i.e., interband excitations are confined to an extremely short time window due to their coupling to the intraband motion, is responsible for the enhancement of the interband HHG and the anomalous carrier-envelope phase dependence observed in recent experiments on semiconductors. The results give the answers of how inter- and intraband dynamics are coupled together and why the interband polarization can dominate the HHG emission in many semiconductors which is a highly debated topic in the community.